Synthesis & identification some heterocyclic compounds derivatives of Biotin - Nabeel A.A.AL. Retha; Ali M. Farhan (Al-Qadisiyah Journal of Pure Science, 2017)
The studies involves synehesis some new derivatives for the biotin by many schemes .The first scheme involve treatment the biotin with methanol in present sulfuric acid concentration to obtained the derivative [H1], the derivative [H1] has been treated with hydrazine hydrate to obtained the derivative [H2] , for there treatment the derivative [H2] with acetyl acetone to obtained the derivative [H3] , and also treated the derivative [181] with carbon disulphide in present potassium hydroxide obtained the derivative [H4] .Either the second scheme involves treat ment the biotin with thiosemacarbazide in present Phosphorous oxy chloride to obtained the derivative [H5] which treated with Phthalic anhydride and Malic anhydride to obtained the derivatives [H6] & [H7] respectively, and also treatment the derivative [H5] with P-N,N-Dimethyl amino benzaldehyde to obtained on Schiff base the derivative [H8] which consider intermediate to preparation the derivative [H9] after with treatment Thio acetic acid .